Survival and persistence of Nipah virus in blood and tissue culture media. Issue 1 (1st January 2019) - Smither, Sophie J.; Eastaugh, Lin S.; Findlay, James S.; O'Brien, Lyn M.; Thom, Ruth; Lever, Mark S.
ABSTRACT: Nipah virus (NiV) infection is a newly emerging zoonosis that causes severe disease in humans. Nipah virus is one of the lesser studied of the WHO emerging pathogens for which research is a priority. Survival and persistence data is important for risk management and understanding the hazard of the virus for laboratory and health care workers that may work with the virus and we present some initial findings on the survival of Nipah virus in blood and tissue culture media under different conditions. The titre of Nipah virus in blood or media at two different temperatures and exposed or sealed to the atmosphere was measured every day for three days and after a week. Nipah virus was very stable in blood in closed tubes held at room temperature with minimal decay over seven days. Decay was observed in all the other conditions tested and was more rapid in samples exposed to the atmosphere. Persistence data is useful for safety planning and risk management.